Size reduction characteristics of black pepper - T J Zachariah, Vikram Vikram, S Balasubramanian, R Kumar, K K Singh, (Journal of Spices and Aromatic Crops, 2013)
Black pepper corn at three moisture contents (5.5%, 11.4% & 17.6%, d.b.) was subjected to size reduction using micro pulverizer with screen aperture size (0.5 mm, 1.0 mm & 1.5 mm) and feed rate (8, 16 & 24 kg h-1) at constant rotor speed (3000 rpm). It was found that the specific energy consumptions showed a decreasing trend (310.71–30.55 kJ kg-1) with increase of feed rate but increasing trend with moisture content and screen openings. Maximum specific energy consumption was recorded for 11.4% moisture content and 8 kg h-1 feed rate with 1.0 mm screen aperture size. The average particle size increased from 0.21 mm to 0.29 mm with increase of moisture content and screen opening. The Bond’s work index (0.086–0.312 kWh kg-1) and Kick’s constant (0.68 to 20.33 kWh kg-1) showed direct motion with moisture content feed rate and screen aperture size. Size reduction ratio and grinding effectiveness of black pepper seed decreased from 25.42 to 14.57 and 0.077 to 0.008 with the increase in moisture content, feed rate and screen aperture size. The loose and compact bulk densities varied in the range of 322.8 to 1408 kgm-3 and 346.2 to 1760 kg m-3, respectively for various mass fractions of sieve analysis. Bond’s work index and Kick’s constants were affected significantly (P<0.05) by moisture content but not feed rate for all screen aperture size.